2007
DOI: 10.1203/pdr.0b013e318030d1cf
|View full text |Cite
|
Sign up to set email alerts
|

Partial Rescue of Retinal Function and Sterol Steady-State in a Rat Model of Smith-Lemli-Opitz Syndrome

Abstract: ABSTRACT:The Smith-Lemli-Opitz syndrome (SLOS) is the firstdescribed in a growing family of hereditary defects in cholesterol biosynthesis, and presents with a spectrum of serious abnormalities, including multiple dysmorphologies, failure to thrive, cognitive and behavioral impairments, and retinopathy. Using a pharmacologically induced rat model of SLOS that exhibits key hallmarks of the disease, including progressive retinal degeneration and dysfunction, we show that a high-cholesterol diet can substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 33 publications
(51 reference statements)
8
43
1
Order By: Relevance
“…It should be noted that our in vitro studies of rhodopsin regeneration were performed in the presence of excess exogenous 11-cis retinal; hence, the decreased regeneration cannot be due to insufficient retinoid availability. Reduction in the regenerability of rhodoposin also would be expected to negatively impact the efficiency of phototransduction and, hence, photoreceptor function, consistent with our prior in vivo observations with the SLOS rat model (7,8,15). We speculate that opsinʼs ability to assume a conformational state requisite for optimal regeneration is impaired as a consequence of alterations in membrane lipid composition and biophysical properties (e.g., fluidity), such alterations being more extensive by 3 months than by 1 month of exposure of rats to AY9944.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It should be noted that our in vitro studies of rhodopsin regeneration were performed in the presence of excess exogenous 11-cis retinal; hence, the decreased regeneration cannot be due to insufficient retinoid availability. Reduction in the regenerability of rhodoposin also would be expected to negatively impact the efficiency of phototransduction and, hence, photoreceptor function, consistent with our prior in vivo observations with the SLOS rat model (7,8,15). We speculate that opsinʼs ability to assume a conformational state requisite for optimal regeneration is impaired as a consequence of alterations in membrane lipid composition and biophysical properties (e.g., fluidity), such alterations being more extensive by 3 months than by 1 month of exposure of rats to AY9944.…”
Section: Discussionsupporting
confidence: 87%
“…It is tempting to speculate that faced with a metabolic insult (such as disrupting normal Chol biosynthesis), the cell responds by globally remodeling its membrane lipidome in an effort to preserve cellular integrity and function, including preservation of membrane fluidity that is critical to the function of a host of membrane-associated enzymes, receptors, and ion channels (40). However, although the retinal photoreceptor cells may be able to tolerate this level of stress for at least 1 month, eventually they lose physiological competence and cellular integrity, undergoing degeneration and cell death by 3 months of exposure to AY9944 (8,15). At that point, rod and cone electrophysiology and structure are severely compromised, and this also correlates temporally with the dramatic losses in the DHA content of ROS membranes documented in this study, as well as those recently reported under virtually identical conditions for whole retina (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolf-Clauw et al (35)(36)(37)(38) and Xu et al ( 39 ) generated animal models of SLOS by treating rats with AY9944 or with a related DHCR7 inhibitor, BM15766; however, postnatal viability was limited. Subsequently, the AY9944-induced SLOS rat model was improved by Fliesler and coworkers, such that postnatal viability was extended to at least three months (40)(41)(42). This was necessary in order to be able to characterize the onset and progression of the biochemical, morphological, and electrophysiological features of the retinal degeneration that occurs in this model, since the rodent retina undergoes substantial development over the fi rst several weeks of postnatal life ( 41,42 ).…”
Section: Isolation Of Oxysterols From Brain Tissues Of Ay9944-treatedmentioning
confidence: 99%
“…However, the same is not true for the retina, at least under conditions where normal cholesterol metabolism has been perturbed. In fact, in an aforementioned rat model of SLOS, feeding a high-cholesterol diet (2%, by weight) was effective in nearly normalizing the cholesterol content of the retina, with a concomitant normalizing trend in the electrophysiological competence of the retina, particularly as involves cone-mediated visual transduction ( 13 ). Attempts to "load" the retina of normal rats by similar dietary cholesterol supplementation have not proved successful (S.J.…”
Section: Does the Retina Require Cholesterol To Achieve Normal Structmentioning
confidence: 99%